Tantangan Dalam Perawatan Stomatitis Uremia Pada Pasien Dengan Penyakit Ginjal Kronis - Adi Ahmad Yusuf; Yanie Febby Martina Lefaan; Riani Setiadhi (Denta Journal Kedokteran Gigi, 2022)
Background: Uremic stomatitis is a rare oral manifestation of chronic and acute kidney disease. The incidence of uremic stomatitis is low, especially because process disease develops gradually over years and occurs in advanced renal failure. This disease is associated with high levels of blood urea. There are four forms of uremic stomatitis that have been identified, namely ulcerative, erythemopultaceous, hyperkeratotic and hemorrhagic. Usually the lesions were seen on buccal mucosa, dorsal or ventral surface of tongue, gingiva, lips and floor of mouth. Purpose: To discuss the challenges in treating uremic stomatitis patient with poor systemic condition. Case: A 73 year old male patient was referred from cardiology department to oral medicine department because there were painful lesions on lips, tongue, palate and buccal mucosa. He was a chronic kidney disease patient whose laboratory results showed high urea and creatinine values. Case management: The Patient was given oral hygiene instruction to clean his teeth and tongue with a gauze soaked in NaCl at least three times a day, compressing the lips and rinse with chlorine dioxide based mouthwash (Oxyfresh®, USA) three times a day. The improvement of oral lesions were not significant because the blood urea and creatinine value were still high. Conclusion: Management of uremic stomatitis needs multidisciplinary teamwork in order to achieve the kidney function and other comorbidities improvement as well as oral lesions to improve the quality of life.